2008
DOI: 10.1111/j.1751-1097.2007.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeine on UVB‐induced Carcinogenesis, Apoptosis, and the Elimination of UVB‐induced Patches of p53 Mutant Epidermal Cells in SKH‐1 Mice

Abstract: Oral administration of green tea or caffeine to SKH-1 mice during UVB irradiation for several months inhibited the formation of skin cancer. Similar effects were observed when green tea or caffeine was given to tumor-free UVB-initiated mice with a high risk of developing skin tumors in the absence of further UVB irradiation (high risk mice). Mechanistic studies indicated that topical application of caffeine stimulated UVB-induced apoptosis as well as apoptosis in UVB-induced focal hyperplasia and tumors in tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…If the DNA damage is not repaired or the damaged cells are not eliminated by apoptosis, the consequences can be cell transformation, uncontrolled proliferation, and eventually skin Family history of melanoma, % 3 tumor formation (29). Mouse studies have shown that oral or topical caffeine administration promotes elimination of UVdamaged keratinocytes (the cells from which nonmelanoma skin cancer arises) via apoptosis and markedly reduces the risk of subsequent skin cancer development (8,(30)(31)(32). The mechanisms and molecular targets for the proapoptotic effect of caffeine after DNA damage have been investigated in cultured cell lines (human osteosarcoma cells).…”
Section: Discussionmentioning
confidence: 99%
“…If the DNA damage is not repaired or the damaged cells are not eliminated by apoptosis, the consequences can be cell transformation, uncontrolled proliferation, and eventually skin Family history of melanoma, % 3 tumor formation (29). Mouse studies have shown that oral or topical caffeine administration promotes elimination of UVdamaged keratinocytes (the cells from which nonmelanoma skin cancer arises) via apoptosis and markedly reduces the risk of subsequent skin cancer development (8,(30)(31)(32). The mechanisms and molecular targets for the proapoptotic effect of caffeine after DNA damage have been investigated in cultured cell lines (human osteosarcoma cells).…”
Section: Discussionmentioning
confidence: 99%
“…A aplicação tópica de cafeína em ratos após submissão à irradiação UV indica que essa substância também é capaz de diminuir o dano ao DNA, a lesão de queratinócitos e a fotocarcinogênese (Koo et al, 2007;Cooney et al, 2008;Lou et al, 2010;Szeto e Tong, 2010).…”
Section: Introductionunclassified
“…We have previously shown that the mTOR/PI3K inhibitor, BGT226, is able to reduce tumour growth rates in mice transplanted with SCC cells (19). In the present study, mice were injected with SCC25 cells and when the tumours were between 4 to 5 mm in diameter we treated them with i) vehicle, ii) 0.5 mg/kg doxorubicin i.p.…”
Section: The Sphk1 Specific Inhibitor Sk1-i (Bml-ei411) Sensitises mentioning
confidence: 99%
“…UV can also activate CD95 death receptor signaling pathways independent of its natural ligand CD95L [17]. The subsequent formation of a death-inducing signaling complex (DISC) is characteristic of death receptor-mediated apoptosis in response to UV radiation [18,19]. Activation of death receptor signaling ultimately activates the initiator pro-caspases-8/-10 leading to the eventual activation of downstream effector procaspases -3,-6,-7 [12].…”
Section: Sunburn Cells (Uv-induced Cell Death)mentioning
confidence: 99%
See 1 more Smart Citation